Problems and prospects of medicinal plant cultivation in Thiruvananthapuram district - Allan Thomas (Department of Agricultural Extension, College of Agriculture, 2000)
A research study entitled "Problems and prospects of medicinal plant cultivation in Thiruvananthapuram district" was undertaken with a view to assess the knowledge of the medicinal plant cultivators on the medicinal value of the plants cultivated by them, to identify the training need of the cultivators in medicinal plant cultivation, to study the market orientation of the cultivators, to analyse the cost-benefit relationship of medicinal plant cultivation and to identify the problems and solutions in medicinal plant cultivation. One hundred medicinal plant cultivators were selected from the four taluks of Thiruvananthapuram district using stratified random sampling technique with proportionate allocation. Data were collected by using a structured interview schedule. Knowledge was assessed by developing a knowledge test for the study. Training need was identified using the method developed by Bhatnagar (1987). Market orientation was studied by using the method developed by Anantharaman (1991), which included identification of marketing channels and analysis of cost- benefit relationship of medicinal plant cultivation by using input-output analysis in terms of economic aspects of medicinal plant cultivation. Problems and solutions in medicinal plant cultivation as perceived by the cultivators, procurers and retail shop dealers were identified by using open-end questions. Ranking was done to identify the importance of the problems and solutions.